Pentahelix collaborative analysis through stakeholder engagement in realizing sustainable environmentally based tourism village governance to support the achievements of the Village SDGs - Eprilianto, Deby Febriyan; Megawati, Suci; Sari, Yuyun Eka Kartika; Pramono, Bambang Sigit; Sari, Lisa Amelia; Rachmadhani, Azzahroh; Febrianti, Eni (2024)
SDGs are a combination of universal and sustainable goals, targets, and indicators that can be applied to measure the reality of development, at the global, national, regional, area, and even village levels. Village SDGs are an integrated effort, one of which is to realize networked villages and culturally responsive villages to accelerate the achievement of the SDGs. The importance of a collaborative approach in village development to reduce village disparities, one of which is in the development of tourist villages. This study will analyze the goals and targets of the 17th Village SDGs, namely Partnership for village development through the role of stakeholders with their involvement in the governance of environmentally-based sustainable tourist villages in Tlemang Village, Indonesia. The method used in this study is descriptive qualitative through direct observation, structured interviews, and documentation studies. The results of this study indicate that stakeholder involvement in the process of environmentally-based tourist village governance is carried out by the government, academics, mass media, communities, and the private sector, each of which has a role consisting of policymakers, coordinators, facilitators, implementers, and accelerators. The success of this collaboration has earned Tlemang Village the title of Intangible Cultural Heritage.